Construct and criterion validity of the Malay Language of Lower Extremity Functional Scale (LEFS) - Mohd Yunus, Muhammad Ariff; Musa, Ramli; Nazri, Mohd Yusof (Elsevier (Singapore) Pte Ltd, 2017)
Objective: The objective of this study is to translate the Lower Extremity Functional Scale (LEFS) into the Malay language and to validate the resulting version.